The high level of aluminum resistance in signalgrass is not associated with known mechanism of external aluminum detoxification in root apices - Wenzl, Peter; Patino, GM; Chavez, Alba L.; Mayer, Jorge Edgard; Rao, Idupulapati M. (Oxford University Press, 2001)
Al resistance of signalgrass (Brachiaria decumbens Stapf cv Basilisk), a widely sown tropical forage grass, is outstanding compared with the closely related ruzigrass (Brachiaria ruziziensis Germain and Evrard cv Common) and Al-resistant genotypes of graminaceous crops such as wheat, triticale, and maize. Secretion of organic acids and phosphate by root apices and alkalinization of the apical rhizosphere are commonly believed to be important mechanisms of Al resistance. However, root apices of signalgrass secreted only moderately larger quantities of organic acids than did those of ruzigrass, and efflux from signalgrass apices was three to 30 times smaller than from apices of Al-resistant genotypes of buckwheat, maize, and wheat (all much more sensitive to Al than signalgrass). In the presence, but not absence, of Al, root apices of signalgrass alkalinized the rhizosphere more than did those of ruzigrass. The latter was associated with a shortening of the alkalinizing zone in Al-intoxicated apices of ruzigrass, indicating that differences in alkalinizing power were a consequence, not a cause of, differential Al resistance. These data indicate that the main mechanism of Al resistance in signalgrass does not involve external detoxification of Al. Therefore, highly effective resistance mechanisms based on different physiological strategies appear to operate in this species.